2000
DOI: 10.1097/00007890-200005150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Protocol Renal Allograft Biopsies and the Design of Clinical Trials Aimed to Prevent or Treat Chronic Allograft Nephropathy1

Abstract: Protocol biopsies may allow a reduction of sample size and especially the time of follow-up in a trial aimed to prevent CAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 26 publications
3
59
1
1
Order By: Relevance
“…Interstitial fibrosis and tubular atrophy that are detected as early as 3 to 6 mo posttransplantation in well-functioning transplants are correlates of later allograft dysfunction and loss (9,19,27,35,41). Similarly, increased chronic scores reported with the CADI system at 1 yr (40) or 2 yr (39) have been correlated with graft losses at 3 and 6 yr, respectively.…”
Section: Significance Of Interstitial Fibrosis and Tubular Atrophy Inmentioning
confidence: 95%
See 1 more Smart Citation
“…Interstitial fibrosis and tubular atrophy that are detected as early as 3 to 6 mo posttransplantation in well-functioning transplants are correlates of later allograft dysfunction and loss (9,19,27,35,41). Similarly, increased chronic scores reported with the CADI system at 1 yr (40) or 2 yr (39) have been correlated with graft losses at 3 and 6 yr, respectively.…”
Section: Significance Of Interstitial Fibrosis and Tubular Atrophy Inmentioning
confidence: 95%
“…The detection of interstitial fibrosis and tubular atrophy remains a useful end point for clinical trials (42), and quantitative methods of interstitial fibrosis assessment likely will improve on its predictive value (32-34). Finally, secondary prevention trials that enter patients with interstitial fibrosis should markedly reduce the number of patients required to detect a change in the rate of graft loss (33,40,41).…”
Section: Significance Of Interstitial Fibrosis and Tubular Atrophy Inmentioning
confidence: 99%
“…Evidence suggests that the first few months after transplantation are critical in the development of CAN and that protocol biopsies may be a valuable means of detecting early signs of chronic allograft damage that have yet to become clinically apparent. In particular, early protocol biopsies have shown that the presence of tubulointerstitial damage and vascular chronic damage are powerful predictors of allograft survival (16). Furthermore, serial protocol biopsies have shown that both interstitial and vascular chronic damage rapidly increase during the first 6 mo after transplantation, then slowly thereafter (17).…”
Section: Diagnosis Of Can By Protocol Biopsymentioning
confidence: 99%
“…Serón et al (16) estimated the minimum sample size of a clinical trial using the presence/absence of CAN in a protocol biopsy at 3 mo posttransplantation as the primary efficacy variable. Power calculations suggested that approximately 300 patients in each of the treatment and placebo groups would be necessary to detect a 50% reduction in the incidence of CAN at 3 mo.…”
Section: Use Of Protocol Biopsies In Clinical Trials Designed To Prevmentioning
confidence: 99%
“…At the molecular level, no differences were found in the extent of protein deposition of TGF-␤ and interstitial collagens, as well as cortical mRNA levels of TGF-␤ and collagens ␣1(I) and ␣1(III) (20). The histologic features of CAN, although most often mild, may occur early after renal transplantation, with a reported prevalence up to 40% in surveillance biopsies performed as early as 3 mo after transplantation (21,22). Treatment of SAR in 1-, 2-, or 3-mo protocol biopsies support the clinical relevance of early detection and treatment of SAR (9).…”
mentioning
confidence: 99%